Tinjauan Yuridis Tindak Pidana Pencabulan Terhadap Anak - I Gusti Ngurah Agung Sweca Brahmanta; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Fakultas Hukum Universitas Warmadewa, 2021)
The increasing crime rate in Indonesia has resulted in the emergence of various modus operandi in the occurrence of criminal acts, one of which is the crime of child molestation. Child molestation can damage the order of family life, the community environment and the school environment, even directly or indirectly a threat to the continuity of development and the future of children who are the next generation of the Indonesian nation and state. The research is to determine the qualifications of acts of sexual abuse against children in the view of criminal law and to determine the application of the law to perpetrators of criminal acts of sexual abuse against minors. The research method used is normative legal research. Issues are discussed based on the laws and regulations. Legal materials use primary and secondary legal materials. The conclusion of this study is the qualification of acts of sexual abuse against children in the view of criminal law. The application of law against perpetrators of criminal acts of obscenity against minors, namely by providing sanctions in accordance with Law no. 23 of 2002 concerning Child Protection, including the provision of imprisonment and fines.